Walden, the Humanities, and the Classroom as Public Space - Case, Kristen (Maine Policy Review, 2015)
Kristen Case describes the kinds of practices that take place in humanities classrooms and shows how these practices are connected to the possibilities of our broader social life. She argues for the humanities classroom as a compromised, beleaguered, fragile, and ephemeral, but nonetheless vital space of actual freedom and suggests that the question of who gets to access this space is one that should be of concern to all of us.